Principles and methods of organization of the sensory garden taking into account visitors — persons with disabilities - Obynochna, Zoriana (Theory and practice of design, 2022)
Human being is always in interaction with the environment and nature. In this context, the psychological, physical and biological needs of people should be covered as best as possible. Gardens are the unique forms of the human connection with nature. In the world the practice of creating sensory gardens is quite successful. Scientists have proven the positive therapeutic effect of sensory gardens on the human body. The article presents the principles and methods of organizing a sensory garden, taking into account visitors, people with disabilities. These included the principle of accessibility; the principle of focusing on a specific area of the senses; the principle of equal use; the principle of psycho-emotional orientation. The analysis of the research on this topic has shown that the natural environment improves the physical and emotional health, sensory gardens create an ideal place for relaxation, meditation, learning and therapy. Each of the principles pointed by the author is considered, the methods of creating sensory gardens for people with disabilities are presented, as well as the typology of sensory gardens according to the sensory principle and the type of human impact. The purpose of the study is to provide the principles and methods of organizing a sensory garden, taking into account visitors — people with disabilities. Methodology. The methodological apparatus to which the author refers during this research is based on the method of complex functional and structural analysis. Critical analysis, comparative method, historical method, complex analysis of factors and factors of influence are used. The novelty lies in the detection of the principles of organization of the sensory garden, taking into account people with disabilities: people with visual, hearing impairments, autism spectrum disorders, cerebral palsy and others. The practical value of the research stands for the implementation of its results into the academic program of the architectural Universities, that can help students-architects in their future professional activities, as well as during the organization of the gardens on the territory of educational, health and recreational institutions.